2020
DOI: 10.1186/s13750-020-00200-0
|View full text |Cite
|
Sign up to set email alerts
|

How does sediment exposure affect corals? A systematic review protocol

Abstract: Background Local management action to address coral-reef stressors can improve reef health and mitigate the effects of global climate change. Coastal development and runoff lead to sedimentation, which directly impacts coral recruitment, growth, mortality, and the ecosystem services that coral reefs provide. Decision making for reef resilience in the face of global and local stressors requires information on thresholds for management action. In response to needs identified by reef managers, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 28 publications
0
15
0
2
Order By: Relevance
“…In this study, different prokaryotic and eukaryotic microbiomes were found across different coral genera in healthy vs. bleached conditions. The greatest alpha diversity of prokaryotic OTUs was observed in sediments beneath the corals, which previous research reported the sediment may affect coral rates of growth, photosynthesis, larval settlement and survival, coral bleaching, and mortality (Tuttle et al, 2020). Sediment bacteria could play a role providing and/or recycling nutrient resources for coral growth/reproduction.…”
Section: Discussionmentioning
confidence: 74%
“…In this study, different prokaryotic and eukaryotic microbiomes were found across different coral genera in healthy vs. bleached conditions. The greatest alpha diversity of prokaryotic OTUs was observed in sediments beneath the corals, which previous research reported the sediment may affect coral rates of growth, photosynthesis, larval settlement and survival, coral bleaching, and mortality (Tuttle et al, 2020). Sediment bacteria could play a role providing and/or recycling nutrient resources for coral growth/reproduction.…”
Section: Discussionmentioning
confidence: 74%
“…Few deviations were made from the previously published, a priori systematic review protocol [ 30 ]. Given that we employed a small team, we provide more detail about how we ensured repeatable and consistent decisions during different stages of the review, especially article screening, data extraction, and study validity assessment.…”
Section: Methodsmentioning
confidence: 99%
“…These additional genera were important because of their importance in the Pacific region under U.S. jurisdiction, as indicated by our NOAA advisory team: Alveopora, Astreopora, Favia, Favites, Goniastrea, Goniopora, Leptastrea, Leptoria, Lobophyllia, Millepora, Platygyra, Pocillopora, and Turbinaria . The following search string in English uses Boolean operators and wildcards to improve the quality (i.e., true positive results) of search results and was tested for its comprehensiveness [ 30 ], shown in Additional file 2 along with slight modifications to the syntax of the search term, which were necessary for different databases:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, recovery and stabilization of coral cover was attributed to reduced sedimentation from watershed restoration [87]. While recovery is possible, certain taxonomic groups of corals have different thresholds of sediment exposure, including concentration, duration, and frequency; therefore, coral community composition may be determined by species-specific sediment tolerance thresholds [88]. Alongside coastal development, sediment exposure is amplified from dredging activity and has both synergistic and antagonistic effects with thermal stress from global climate change [89].…”
Section: Human Use: Tourism and Coastal Developmentmentioning
confidence: 99%